UKURAN PERUSAHAAN MEMODERASI PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Aprih Santoso; Teti Susilowati (Politeknik Negeri Malang, 2019)
The purpose of this study is to analyze the effect of capital structure (debt equity ratio / DER) on firm value (per book value / PBV) with firm size (SIZE) as a moderating variable. This study uses secondary data obtained from LQ 45 companies listed on the Indonesia Stock Exchange in 2015-2018. The population in this study is LQ 45 companies listed on the Indonesia Stock Exchange in the period 2015-2018. The reasons or sample selection based on certain criteria are based on: Companies that are LQ 45 companies listed on the Indonesia Stock Exchange during the 2015-2018 period and who already have and submit complete financial statement data so that the sample data processed is 120 companies (35 companies x 4 research periods). T test results indicate that the capital structure has a negative effect on company milai. The moderation test results in this study turned out that the size of the company moderates (strengthens) the relationship between capital structure and firm value.